La mala calidad de sueño se asocia a una menor adherencia al tratamiento antirretroviral de gran actividad en pacientes peruanos con infección por VIH/SIDA - Tello Velásquez, Jorge Renzo (2015)
This cross-sectional study analyzed the association between poor quality of sleep and adherence to highly active antiretroviral therapy (HAART) in 389 Peruvian patients with HIV/AIDS. Poor quality of sleep was measured with the Pittsburgh Sleep Quality Index (PSQI) and adherence with the CEAT-VIH (Peruvian adaptation). A Poisson generalized linear model with robust standard errors was used to estimate prevalence ratios and 95%CI. A crude model showed that mild, moderate, and severe poor quality of sleep were associated with inadequate treatment adherence. In the adjusted model for variables associated in the bivariate analysis or variables theoretically associated with adherence, only moderate/severe poor quality of sleep remained associated (PR = 1.34, 95%CI: 1.17-1.54; and PR = 1.34, 95%CI: 1.16-1.57, respectively). The study concluded that moderate/severe poor quality of sleep was independently associated with adherence to HAART. Assessing quality of sleep may be helpful in the comprehensive evaluation of HIV patients.